Mean Length of Utterance of Children at the Trihita Alam Eco School - Ari Laras Utami, Anak Agung Istri; Sudipa, I Nengah (Humanis; Vol 25 No 3 (2021)DO - 10.24843/JH.2021.v25.i03.p04, 2021)
The aim of the study is mainly at testing the theory of Brown on the Mean Length of Utterance (MLU). Methods applied in this study were observation and audio recording technique. The data in this study were the utterances produced by students of Trihita Alam Eco School. There were sixteen children ranging from 4 to 6 years participating in this study (M=5.4). The children observed in this study are healthy children both physically and psychologically. The written permission from the school has been obtained to conduct the study. The results show that the sentence structures produced by children are quite well-organized and are able to place language functions clearly. The calculation of the MLU value in the research subjects show that Brown's theory which states that children at age 47 months have the MLU of 4.5 are mostly correct. The assumption that children who have the same ages doesn’t imply that they have the same MLU is proven right.